1994
DOI: 10.1136/bjo.78.6.458
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex keratitis in children.

Abstract: Ophthalmic findings are reported in 31 eyes of 28 children with herpes simplex keratitis. Twenty two had dendritic ulcers, and nine had geographic ulcers or disciform stromal keratitis. After resolution of keratitis, 80% (19/22) of children with dendritic ulcers achieved corrected visual acuity of6/9 or better, 50% (11/22) had induced astigmatism, 45% (9/22) had one to five recurrences. In the group with geographic or disciform lesions, 89% (8/9) had reduced corrected vision, 78% (7/9) had induced astigmatism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 11 publications
1
21
2
Order By: Relevance
“…The rate of bilateral involvement in the larger series of children was 10%226% 3,4,6,8 (Table 2), which is higher than one would expect in a similar cohort of adults 2,13,14 and higher than that in our series. In our series of 29 children, only 1 patient (3%) had bilateral keratitis.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The rate of bilateral involvement in the larger series of children was 10%226% 3,4,6,8 (Table 2), which is higher than one would expect in a similar cohort of adults 2,13,14 and higher than that in our series. In our series of 29 children, only 1 patient (3%) had bilateral keratitis.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, in about 80% of our patients the keratitis was recurrent in nature. The recurrence rate in children was also higher in previous reports [3][4][5][6][7][8] (Table 2) than one would expect in a similar cohort of adults. 1,[15][16][17][18][19] On the basis of the Kaplan-Meier estimator, median recurrence time (ie, the time needed for an ocular recurrence to develop in 50% of patients) was 47 months of follow-up in our study; in contrast to the 12 months of followup found by Chong et al 8 Two possible reasons may explain why the recurrence interval in our study is longer.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Brief taken into consideration for individuals who have been diagnosed use of a weak topical corticosteroid, such as loteprednol etabonate with atypical herpes simplex keratitis unresponsive to antiviral ophthalmic solution (Alrex ® ) can be used in more severe cases, therapy, as dendritiform lesions can present in both forms of and oral antihistamines, nasal corticosteroids, and nasal cromolyn keratitis. [3] Beigi and colleagues [4] found that children who develsodium are indicated for the other symptoms of allergy.…”
Section: Clinical Presentation Of Ocular Inflammationmentioning
confidence: 99%
“…3 Although most often unilateral, herpetic keratitis in children can affect both eyes and bilateral involvement has been described in 10% to 26% of children. 2,3,[17][18][19][20] Neonatal herpetic ocular infection, in contrast is frequently bilateral and tends to occur between 2 days to 2 weeks of age. 21 In 30% of cases, mothers of infected neonates show signs or symptoms of HSV genital infection at the time of delivery.…”
Section: ' Epidemiologymentioning
confidence: 99%